Religious coping, stigma, and psychological functioning among HIV-positive African American women - Hickman, Enith E. (Mental health, religion & culture, 2013)
The present study examined the role of religious coping in psychological distress and adjustment both cross-sectionally and longitudinally among 141 HIV-positive African American women. Cross-sectional analyses showed that negative religious coping was associated with poorer mental health and functioning, and greater perceptions of stigma and discrimination. Longitudinal analyses revealed that greater negative religious coping at baseline significantly predicted greater changes in mental health in a negative direction 12 months later. Positive religious coping was not associated with any measures of psychological well-being, nor did it predict any mental health outcomes at 12 months. However, participants who experienced high levels of HIV-related stigma and reported high levels of positive religious coping were less depressed than those who reported lower levels of positive religious coping. These results suggest that for this population, negative religious coping was a more salient determinant of psychological distress than positive religious coping was of psychological health.